Pemahaman Musibah dalam Al-Qur’an dan Hadis untuk Pengajaran Al-Qur’an dan Hadis - Mursidin, Ida Ilmiah (AIJER: Algazali International Journal Of Educational Research, 2024)
This study explores the meaning of Musibah in the Qur'an and its Hadiths to provide understanding in learning. It elaborates on the meaning, forms, and urgency of Musibah in the Qur'an and Hadiths concerning Musibah. The type of research used is qualitative using the library research method. This study concludes that not all Musibah connotes negativity as Musibah can also be related to goodness. The forms of Musibah are depicted in the verses of the Qur'an, such as Musibah occurring due to human actions, including sins, as mentioned in QS. Asy-Syura/42:30. There are many other Qur'anic verses that discuss Musibah. Understanding the meaning of Musibah can assist in the process of learning the Qur'an and Hadith.